EVALUASI KELAYAKAN USAHATANI BERAS MERAH (Oryza Nivara) DI DESA MANIS RAYA KECAMATAN SEPAUK KABUPATEN SINTANG - MASWADI, MASTORDIANTO, ADI SUYATNO, (Jurnal Social Economic of Agriculture, 2019)
Manis Raya village is one of the villages in the subdistrict of Sepauk having production of Oryza Nivara is large enough. The size of the production Oryza Nevara does not yet guarantee a high income are accepted by farmers. Production of Oryza Nevara obtained in the village Manis Raya relatively hight, does not mean the income is also hight, so that required a research analisis income and feasibility farming of Oryza Nivara in the village of Manis Raya. Research aims to know the income and feasibility farming of Oryza Nivara that was held in April until June 2018. The determination of locations have done by deliberately (purposive) with consideration that the village of  Manis Raya is one of producer Oryza Nivara. The analysis used in this research was income analysis and feasibility. The result of the analysis showed that the average income of Oryza Nivara farmers for one growing season is Rp. 17.098.414 /ha mt growing season. The analysis showed revenue of cost ratio was 4,54, thus, Oryza Nivara farm in the village of Manis Raya worth to be the efforted.Keywords: Analysis of income, farming Oryza Nivara, feasibility analysis.